Penitence and Peace-Making in City and Contado: The Bianchi of 1399 - Webb, Diana M. (Studies in church history, 1979)
A major trend in the recent historiography of medieval and renaissance Italy has been towards the reassertion of the fundamental importance of the countryside and of agriculture. This is not so much to deny the unique position occupied by the cities in Italian life as to remind us of some essential features of those cities and of the men who ruled them. Towns were more typically market centres for their localities than entrepôts of long-distance commerce; while many members of both the higher and the lower urban social strata carried with them throughout life a status ultimately derived from the status they or their forebears occupied or had occupied in rural life. Conversely, the members of, say, the Florentine urban patriciate around the year 1400 were almost to a man landlords in the surrounding countryside. They were also of course the men who made the laws, levied taxation and generally controlled the government of the countryside as of the town. At every level of life we have to postulate an intimacy of relations between town and country which the conditions of modern urban life can make it an effort even to imagine.